2005
DOI: 10.1016/j.acn.2005.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental psychometric status of neuropsychological batteries

Abstract: A fundamental requirement for neuropsychological assessment is dependability. Neuropsychological knowledge is dependable only if it has been validated using psychometric methods. Since batteries are used for interpretations, the psychometric validation methods that are acceptable for individual tests must be applied to batteries to produce dependable information. While the standardized battery has been validated, the flexible battery has not. Due to the probability that some tests will be impaired by chance, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 24 publications
0
34
0
4
Order By: Relevance
“…These authors (Hom 2003;Russell et al 2005) have opined that unlike the flexible battery, if all the tests in the fixed battery have been normed on the same sample, then this allows the clinician to more clearly understand the interrelationships between test scores because there is less error related to sampling differences. Moreover, according to them, because research has compared the fixed battery's normative sample to the performance of individuals with confirmed brain impairments (of differing etiologies), the fixed battery uniquely allows examiners to empirically differentiate whether the litigant's pattern of test results is more consistent with those with confirmed brain impairments versus nonbrain impairment.…”
Section: The Legal Implications Of Fixed and Flexible Test Batteries mentioning
confidence: 96%
See 3 more Smart Citations
“…These authors (Hom 2003;Russell et al 2005) have opined that unlike the flexible battery, if all the tests in the fixed battery have been normed on the same sample, then this allows the clinician to more clearly understand the interrelationships between test scores because there is less error related to sampling differences. Moreover, according to them, because research has compared the fixed battery's normative sample to the performance of individuals with confirmed brain impairments (of differing etiologies), the fixed battery uniquely allows examiners to empirically differentiate whether the litigant's pattern of test results is more consistent with those with confirmed brain impairments versus nonbrain impairment.…”
Section: The Legal Implications Of Fixed and Flexible Test Batteries mentioning
confidence: 96%
“…The juxtaposition of the assertions of Hom (2003) and Russell et al (2005) and Bigler (2007) may have left some neuropsychologists to question whether a flexible test batter will be admissible in those courts that require the Daubert standard. Moreover, Bigler (2007) has indicated that a few attorneys have begun using these arguments as fodder for "legal maneuvering" by indicating that the "flexible battery approach has never been properly validated and therefore remains unreliable" (p. 46).…”
Section: The Legal Implications Of Fixed and Flexible Test Batteries mentioning
confidence: 97%
See 2 more Smart Citations
“…Within this scope, if several studies reported the number of low test scores [3, 5-8] or low domain scores [17], they did not focus on which specific cognitive tests showed low scores. In fact, beyond the analysis of the number of low test scores, it is primarily the direct comparison between scores across different tests that is utilized for a neuropsychological interpretation [4]. This interpretation of test results could have greater clinical relevance and subsequently help clinicians to more accurately determine the cognitive profile of their patients.…”
Section: Introductionmentioning
confidence: 99%